N-Arylated pyridinium salts having reactive groups - Yamaguchi, Isao; Higashi, Hideo; Shigesue, Sachiko; Shingai, Saki; Sato, Moriyuki (Tetrahedron letters, 2007)
The pyridinium salts having reactive amine and/or pyridyl groups were synthesized by the reaction of Zincke salts with amines. The pyridinium salts having reactive amine and/or pyridyl groups were obtained by the reaction using Zincke salts. Optical properties and anion exchange behavior of the obtained pyridinium salts were investigated.